Colon cancer survival after radical surgery performed in hospitals of the Arkhangelsk region: a population-based analysis - D. V. Bogdanov; A. V. Berezin; E. F. Potekhina; E. A. Mordovsky; M. Yu. Valkov (Сибирский онкологический журнал, 2023)
Background. surgery is the main method of treatment of colon cancer (cc). Radical surgery performed in non-specialized hospitals can lead to the adverse outcomes.The aim of this study was to assess CC survival after radical surgery performed in state hospitals of the arkhangelsk region (North-West Russia) in 2010–21.Material and Methods. data on all the 2142 cases of radical surgery of CC were obtained from the arkhangelsk regional cancer registry (ARCR). One- and five-year cancer-specific survival rates were estimated by the survival tables; cumulative survival function was calculated by the Kaplan–meier method. Univariate and multiple cox regression analysis was carried out to identify independent predictors associated with CC death risk after radical surgery in state hospitals (incl. sex, age at the time of diagnosis, topography, morphology and stage of CC).Results. less than half (42.8 %) of patients underwent surgery at the arkhangelsk clinical cancer center (accc), a single specialized hospital. one- and five-year survival rates of all patients were 86.5 % (95 % CI: 84.9–87.9 %) and 65.1 % (95 % ci: 62.7–67.4 %), respectively. The 5-year survival rate of patients who underwent surgery in the accc was significantly higher than that in patients who underwent surgery in other state non-specialized hospitals (76.0 % (95 % ci: 72.5–79.0 % versus 49.3–73.8 %, p<0.0001). The relative risk of death of CC patients depended on the state hospital where radical surgery was performed and the stage of CC; it did not depend on patients’ sex, morphology and topography of CC.Conclusion. our results demonstrate the need to search for specific reasons for the relatively low survival in patients after radical surgery performed in non-specialized hospitals.